Television, Health, and Happiness: A Natural Experiment in West Germany - Adrian Chadi; Manuel Hoffmann (Institute of Labor Economics (IZA), 2021)
Watching television is the most time-consuming human activity besides work but its role for individual well-being is unclear. Negative consequences portrayed in the literature raise the question whether this popular pastime constitutes an economic good or bad, and hence serves as a prime example of irrational behavior reducing individual health and happiness. Using rich panel data, we are the first to comprehensively address this question by exploiting a large-scale natural experiment in West Germany, where people in geographically restricted areas received commercial TV via terrestrial frequencies. Contrary to previous research, we find no health impact when TV consumption increases. For life satisfaction, we even find positive effects. Additional analyses support the notion that TV is not an economic bad and that non-experimental evidence seems to be driven by negative self-selection.
Keywords: C26; D12; I31; H12; J22; L82; 330; health; happiness; well-being; natural experiment; television consumption; time-use; entertainment; CSPT; ArcGIS; mass media